Effect of mig and tig welding on hybrid structure using modal analysis - Ilmanfaiq, Hamzah (2013)
Nowadays, joining dissimilar metal by using welding are used in manufacturing industries such as automaker industries. While the common use welding types are Tungsten Inert Gas (TIG) and Metal Inert Gas (MIG). The purpose of joining dissimilar metal is to minimize the cost while maximizes the performance and efficiency of a machine or structure by composing the properties of different metal. Therefore, this project was carried out to study the effect of MIG and TIG welding effect to the hybrid structure using modal analysis. This effect can be determined by investigating dynamic characteristic which was obtained using modal analysis. Aluminium 1100 plate and Stainless steel 304 plate were materials that had been chosen to join using MIG and TIG welding. Experimental modal analysis has been done on both dissimilar plates to obtain the dynamic characteristic. Overall, the comparison result between FEA and EMA show a good consistency error between FEA and EMA and range from 1.16 % to 22.52 %. This study also showed that MIG welding produces structures that has higher natural frequencies compare with the structure that was welded by TIG